The Impact of Functional Movement Variability and Movement Creativity on Sport Climbing Performance. - van Bergen, Nikki Geerte; Orth, Dominic; Deschle, Nicolas; Berkenbosch, Robert; van der Toorn, Marthe; Savelsbergh, Geert; van der Kamp, John (European Journal of Sport Science, 2025)
Expertise in sports is underpinned by the ability to adapt to changing individual, task and environmental constraints. The ecological dynamics approach positions movement variability as having functional properties thus enabling adaptation. Additionally, it holds that movement creativity emerges from movement variability in the process of exploration. To test these conjectures, we determined the relationships between movement variability, movement creativity and performance. Twenty‐one male climbers, ranging from experienced to high elite level participated. Functional movement variability and climbing performance were assessed in two different tests. The primary goal of the functional movement variability test was to perform a boulder problem in as many different ways as possible, whereas in the performance test, participants had six attempts to progress as far as possible. 2D hip position data (derived from video recordings using Kinovea) were collected to determine the number of distinct successful trajectories performed (movement variability), the degree of originality of each successful trajectory (movement creativity) and the trajectory length of the best attempt in the performance test (performance). Results revealed that both the ability to exhibit functional movement variability (p = 0.005) and the exploration of movement creativity (p = 0.002) were strongly associated with performance. Movement creativity contributed to performance in addition to movement variability (p = 0.024). We propose that variability is more than just the number of different movements; it should also be understood in how distinctly different these movements are, since they may reflect different patterns of exploration and determine the range of novel adaptations within an individual's capacity to be discovered. Highlights: Movement variability as well as movement creativity are strongly associated with sport climbing performance.Movement creativity independently contributes to climbing performance beyond contributions of the functional movement variability.Movement variability is more than only the number of distinct movements (or the size of the movement repertoire) and also includes a distinction in terms of the breadth and depth of the differences.